RANCANG BANGUN SISTEM INFORMASI UJIAN ONLINE BERBASIS WEB DI MTSS NASRUDDIN DAMPIT - Annurwan; Hari Lugis Purwanto; Wiji Setyaningsih (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2023)
The majority of the school exam systems in this era used a conventional system, namely using paper as a test tool. Even though conventional exam implementation could make it difficult for teachers to correct exam sheets, so it also took a long time to find out the results. In addition, by using exam sheets, it will worsen the environment. So it is hoped that there will be digitization by implementing an online exam system, which can be applied to MTSS Nasruddin Dampit. This study aims to produce a design and application of a website-based online exam information system at MTSS Nasruddin Dampit. From this study it can be concluded that this design model uses UML with the waterfall method. This design model is ultimately able to make it easier for teachers in terms of assessing school exam results because this system can automatically display the results of calculating student exam scores.